(untitled) (Global Scientific Review, 2026)
In order to assess the effects of injection duration (10, 8, 6, 4, 2 before TDC) on emissions, combustion parameters, and CI engine performance once utilizing biodiesel and diesel mixture (B30) at engine speeds of 3000 rpm with a full load, we prepared the AVL Boost model with combustion models Vibe 2 and Woschni 1990 as sub-models and applied numerical analysis. The utilization of various fuel types in compression ignition engines to enhance performance of engine with decreasing exhaust releases was the main emphasis of this study. In this effort, a 4-strokes and 4- cylinders, engine has been utilized. The findings demonstrated that once the time of injection was rated, the effective torque and the braking power both dropped. Biodiesel blends produced less effective power and torque than diesel fuel at all selected time of injection. Biodiesel blends produced less effective power and torque than diesel fuel at all chosen time of injection. Under all operating conditions, biodiesel fuels emit much less soot but more NOx than traditional diesel fuels. For all selected fuels, NOx releases reduced with increasing the soot releases once durations of injection were switched from advanced to rated.